Adapting Corporate Valuation Models to the Technology Sector A Sector-Specific Framework Integrating Intangibles and User-Based Metrics - Deshmukh, Sanika; Bathia, Amit; Mehta, Apurva; Kappal, Jyoti Mehndiratta; Desai, Bineet; Thakker, Hemal (Journal of Theoretical Accounting Research, 2025)
Valuing technology firms poses challenges that are hard for multiples and customary models, such as for example Discounted Cash Flow (DCF), to address also. These approaches are widely used in practice while they rely heavily on concrete assets and short-term cash flows since much of the value embedded in intangibles and user ecosystems is underrepresented. Current practice remains fragmented. Analysts often use extra commentary on user metrics to help DCF or multiples while venture capitalists depend on exit models or scorecards, like monthly active users, ARPU, churn, or SaaS-specific measures like ARR multiples. Yet even these adjustments still lack any standardization. Furthermore, no one systematically integrates these adjustments within valuation models. This study proposes a programmable valuation framework specific for sectors embedding intangible-based measures (R&D capitalization, patent intensity, intangible-to-concrete ratios) and user-based metrics (MAUs, ARPU, CAC, churn) into valuation methodologies. Startups like UiPath and Palantir, growth firms like Shopify and Zoom, and mature giants like Apple and Microsoft show through tests of this framework how integrating the variables bridges the persistent gap from market capitalization to customary valuation outputs. The contribution represents a reproducible structured model as it moves past fragmented adjustments; it gives analysts, investors, plus policymakers a stronger tool for valuing technology-driven enterprises and valuation frameworks.
ISME
Keywords: Tech Valuation; User-based metrics; intangible assets; corporate finance; discounted cash flow